Entanglement Dynamics of Two Trapped Ions in the Intermediate Excitation Regime (Journal of Atomic and Molecular Sciences, 2010)
We have studied the model for interaction of two trapped ions in a trap with a laser beam in the intermediate excitation regime. By applying unitary transformations, the system can be transformed into the Tavis-Cummings model. The entanglement dynamics of two trapped ions in this system has been investigated. With computation of the concurrence, unlike that in Tavis-Cummings model, we find that the entanglement of two ions in our model undergoes periodic death and revivals.